Criminalization for Adultery in Indonesia Comparative Analysis of Article 284 of the 1946 Criminal Code and Article 411 of the Criminal Code No. 1 of 2023 - Muhammad safar; Suci Ramadani; Ismaidar (Yayasan Multidimensi Kreatif, 2024)
Adultery has long been a sensitive and complex legal issue in the Indonesian criminal law system. Article 284 of the 1946 Criminal Code limits the crime of adultery tomarried couples, which can only be processed through a complaint from the legal spouse. However, along with the development of social values, Article 284 is considered inadequate in accommodating the dynamics of modern society. In 2023, Indonesia enacted the Criminal Code No. 1 of 2023, specifically Article 411, which expands the scope of the crime of adultery by including acts of adultery by those who are not married and provides the right to complain to parents or children. This study aims to analyze the comparison between Article 284 of the 1946 Criminal Code and Article 411 of the Criminal Code No. 1 of 2023 in regulating the punishment of adultery perpetrators in Indonesia. The method used is normative juridical with a doctrinal approach to examine the legal substance, identify changes, and examine the social and legal impacts of this reform. The results of the study show that Article 411 provides a broader legal scope and strengthens protection for the injured party. However, the complaint offense mechanism that is maintained poses challenges in implementation, especially related to the potential for abuse of complaint rights and the high burden of proof for law enforcement officers. In conclusion, changes in Article 411 are expected to balance the protection of social norms and respect for individual privacy. The effectiveness of its implementation is highly dependent on the sensitivity of law enforcement officers in implementing this rule fairly and adaptively in the context of diverse Indonesian society.